Innovation in the Development of the Cempalagi Historical Tourism Area Based on a Digital Ecosystem in Bone Regency - Zainal, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study analyzes innovation strategies for developing the Cempalagi historical tourism area based on a digital ecosystem in Bone Regency, South Sulawesi. Located in Mallari Village, Awangpone District, Cempalagi Hill holds significant historical value as the site where Arung Palakka, the 15th King of Bone, made his oath of liberation in the 17th century. Despite its cultural importance, the area faces major challenges, particularly in technology integration and community involvement in digital tourism initiatives. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis. Data were analyzed thematically based on the models of Miles and Huberman as well as Braun and Clarke. The theoretical framework draws from Rickard and Raymond’s theory of community-based tourism (CBT) innovation, digital destination ecosystem concepts and the CBT approach. Findings reveal that innovation in the Cempalagi tourism area remains limited, with minimal technological adoption and weak community engagement. The absence of specific local government policies and underdeveloped digital infrastructure pose significant barriers. However, there are promising opportunities for multistakeholder collaboration, youth participation, and the creative use of digital media to revitalize historical and cultural tourism. This study recommends integrSating local historical narratives into digital platforms, strengthening community capacities, and formulating supportive local tourism policies. Through collaborative and innovative efforts, Cempalagi has the potential to become a digital-based historical tourism icon that reinforces Bone’s cultural identity and broadens its global outreach.